Socio-economic status of fishers in Dal Lake, Kashmir, India - Shakir Ahmad Mir; S.N. Ojha; Ananthan P.S.; Neha W. Qureshi; Shivaji Argade (Journal of Indian Fisheries Association, 2023)
The study investigates the socio-economic status of the fisher community of Dal Lake, which is the second largest lake in district Srinagar of Jammu and Kashmir. The data for the study was collected through a structured interview schedule from 180 respondents from 3 fishing villages located on the periphery of Dal Lake. The results revealed that 63.3% of the fishers belonged to middle age group (35-59), dominated by the male folk (88.9%) and 97.8% were married. The majority of the respondents had no formal literacy (78.9%) and most of them were living in nuclear families (56.7%) with less than 4 family members. The income status of the respondents revealed that 65.6% of them earned a low monthly income from fishing (< Rs. 15000) and the average monthly income per household was Rs. 13,393. The study found that 96.7% of the respondents had own boats and cast net was the dominant gear being used in Dal Lake. It may be surmised that the fishing community was living on the margins, getting very less attention from the government and other developmental organizations. State fisheries department, together with tourism and agriculture department, shall take measures to strengthen the livelihoods of fishers in Dal Lake following a consultative process.